2020
DOI: 10.1080/2162402x.2020.1838141
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating TNFRSF9 + CD8 + T cells define different subsets of clear cell renal cell carcinoma with prognosis and immunotherapeutic response

Abstract: Xu (2020) Tumor-infiltrating TNFRSF9 + CD8 + T cells define different subsets of clear cell renal cell carcinoma with prognosis and immunotherapeutic response,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…A large-scale analysis targeting ccRCC tumors confirmed T cells are the main TIICs within the TME. 45 Overall, higher CD8+ T cell infiltration in ccRCC is associated with worse outcomes, implying that the infiltrating CD8+ T cells might play a critical role in TME. Multiple ccRCC studies have confirmed that these infiltrating CD8+ T cells can be suppressed to become dysfunctional.…”
Section: Discussionmentioning
confidence: 90%
“…A large-scale analysis targeting ccRCC tumors confirmed T cells are the main TIICs within the TME. 45 Overall, higher CD8+ T cell infiltration in ccRCC is associated with worse outcomes, implying that the infiltrating CD8+ T cells might play a critical role in TME. Multiple ccRCC studies have confirmed that these infiltrating CD8+ T cells can be suppressed to become dysfunctional.…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, according to the data published by Gedye et al ( 2016 ), the total number of RCC tumor cells per mm 3 has a minimum value of 2.5 × 10 4 . The median number of CD8+ T cells varies among studies; we used as reference the value obtained by Li et al ( 2020 ) of 84 cells per mm 2 . To obtain the density of the other immune cells, we used the immune cell type absolute fraction data for ccRCC from the Cancer Immunome Atlas (TCIA) database (data available at https://tcia.at/cellTypeFractions ).…”
Section: Methodsmentioning
confidence: 99%
“…Many receptors in the immunoglobulin superfamily (such as CD28, and inducible T cell co-stimulator) and TNF receptor superfamily (TNFSF) exert costimulatory actions [78]. TNFSRF9 is thought to be an antigen stimulation-inducible co-stimulatory receptor, which is transiently expressed on activated CD8 + T, activated CD4 + T, and NK cells [64,79,80]. Co-stimulatory signaling mediated by TNFRSF9 promotes T cell proliferation, secretion of cytokines, resistance to activation-induced cell death, and development of memory T cells [80].…”
Section: Icis Based On T Cell Exhaustion In Rcc-bmmentioning
confidence: 99%
“…Co-stimulatory signaling mediated by TNFRSF9 promotes T cell proliferation, secretion of cytokines, resistance to activation-induced cell death, and development of memory T cells [80]. TNFRSF9 + CD8 + T cells possess both exhaustion (PD-1, TIM-3, CTLA-4, and TIGIT) and effector phenotype (IFN-Îł, granzyme B, and Ki-67) [79]. This dual phenotype of TNFRSF9 + CD8 + T cells indicates that these cells may not be terminally exhausted; however, they could respond to ICB [79].…”
Section: Icis Based On T Cell Exhaustion In Rcc-bmmentioning
confidence: 99%
See 1 more Smart Citation